2013
DOI: 10.1159/000356340
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Intradialytic Exercise and Hemodialysis Adequacy

Abstract: Background/Aims: According to mathematical modeling, intradialytic exercise of sufficient intensity and duration implemented in the second half of dialysis should be as efficacious as increasing dialysis time for dialysis adequacy. This assumption has not been tested in vivo. Methods: In this controlled trial, 11 hemodialysis (HD) patients (mean (SD) age 56 (13) years) were recruited. Each patient completed three trial arms in a randomized order: routine care (CONT), increased HD time of 30 min (TIME), and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 55 publications
1
36
0
6
Order By: Relevance
“…The impact of IDE on Kt/V is inconsistent in the literature, with both positive (Kong et al 1999;Parsons et al 2006) and no changes reported (Afshar et al 2010;Kirkman et al 2013). Compared with the control session, Kt/V was found to be slightly, but significantly greater during the 55% protocol, but not during the 70% protocol.…”
Section: Discussionmentioning
confidence: 73%
“…The impact of IDE on Kt/V is inconsistent in the literature, with both positive (Kong et al 1999;Parsons et al 2006) and no changes reported (Afshar et al 2010;Kirkman et al 2013). Compared with the control session, Kt/V was found to be slightly, but significantly greater during the 55% protocol, but not during the 70% protocol.…”
Section: Discussionmentioning
confidence: 73%
“…Seven of the 13 studies that reported spKt/V urea showed no statistical significance and small effect sizes for intradialytic exercise . Six of the 13 studies that reported spKt/V urea favored intradialytic exercise showing statistical significance and/or a large effect size.…”
Section: Resultsmentioning
confidence: 92%
“…Four studies allowed exercise into the third hour of dialysis . One study specifically prescribed exercise in the last half of dialysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12]18 Intradialytic exercise increases solutes removal by increasing cardiac output, which, combined with higher metabolic need for the exercising muscle, leads to muscle vasodilation. [5][6][7][8][9][10][11][12]18 Intradialytic exercise increases solutes removal by increasing cardiac output, which, combined with higher metabolic need for the exercising muscle, leads to muscle vasodilation.…”
Section: Discussionmentioning
confidence: 99%